Navigating Legal Pluralism: A Comparative Analysis Of Islamic Law And Secular Legal Systems In Pakistan - Muhammad Ishfaq; Samina Yasin; Muzammil Riaz; Kanwal Riaz (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Pakistan's legal landscape is characterized by a complex interplay of various legal systems, including Islamic law (Sharia) and secular legal frameworks inherited from colonial legacies. This paper seeks to explore the dynamics of legal pluralism in Pakistan, focusing on the coexistence and interaction of Islamic law and secular legal systems within the country's judiciary and legal institutions. Through a comparative analysis, the paper aims to examine the historical evolution, sources, principles, and application of both Islamic law and secular legal systems in Pakistan, shedding light on their respective roles, conflicts, and accommodations within the Pakistani legal framework. Additionally, the paper will critically assess the challenges and opportunities posed by legal pluralism in Pakistan, particularly in terms of ensuring justice, rule of law, and human rights in a diverse and rapidly changing society.